Word-of-Mouth in the Context of Internet Mediated Services: the case of Skype - Gavronski, Maarja (2007)
Skype is a contemporary innovative business providing Internet mediated services. More importantly Skype is a company, which because of the business model is highly dependent on its users and at the same time has made word-of-mouth integral to the service, as a way of extending the user base. Therefore, the effect of satisfaction on word-of-mouth was examined, as well as the mediating effect of loyalty on the relationship between satisfaction and word-of-mouth. The second part of the research involved investigating the effect of word-of-mouth on usage. Using data obtained from a sample of Skype users, support was found for all hypothesised relationships with word-of-mouth and usage as the dependent variables. The conclusion includes theoretical discussion of the findings and implications for Skype managers, as well as research limitations and directions for future research.